Using Mouteh Goldmine soil’s cyanobacteria for bioremediation of tailing dam soil - hamid Sodaeizade; fariba hokmollahi; amir hossein nateghi; Manouchehr Mohammadi (علوم محیطی)
Introduction: Natural and human activities lead to soil degradation and soil salinization. In the last two centuries, world metal pollution level has increased extremely. The presence of some heavy metals in aquatic ecosystems is a constant threat to the health of human societies. The decrease of farmlands threatens food security. There are approximately one billion ha salt-affected soils all over of world, which can be utilizable after chemical, physical and biological remediation. Many mines in the world and also in Iran exist and as a result, soil erosion and dust release from waste dams is a matter of concern. Bioremediation using biological agents to detoxify and degradation of environmental pollutants provides a suitable alternative method for substitution of current heavy metals removal strategies..Material and methods: As a result of extraction operations by cyanidation in Mouteh gold mining complex, wastewater and waste soil sediment are widely achieved. In this study soil samples were collected from Mouteh Goldmine tailing dam soil in September 2018. The collected soil samples were cultured in BG11 medium and incubated for microalgae identification and biomass production. Also, 5 g soil was inoculated with 0.5 g biomass of cyanobacteria and the physicochemical characteristics of the soil including pH, Na, K, Pb, and Cd, before and after the inoculation of soil with cyanobacteria were determined.Results and discussion: In this study, cyanobacteria Phormidium tenue Gomont, Osillatoria tenuis C.Agardh ex Gomont, Lyngbya aestuarii Liebman ex Gomont and the green alga, Scenedesmus obliquus (Turpin) Kützing were identified. Culture results of filamentous cyanobacteria on goldmine tailing dam soil showed that cyanobacteria grew easily and produced a significant surface crust. The results of the physical analysis of the soil samples showed that O. tenuis decreased Na as a salinity element, and P. tenue absorbed high amounts of Pb as a heavy metal pollution element. Mouteh Goldmine soil cyanobacteria, Osillatoria tenuis and Phormidium tenue, could play a role in mine recovery from salinity and heavy metals and in mine tailing dam soil bioremediation. They can also prevent soil erosion and dust release from waste dams. Conclusion: Dust release from waste dams can affect the health of living organisms like mining workers, plants, and even soil microalgae that are close to the mine. Cyanobacteria create biological soil crust and the results of this research showed that cyanobacteria, especially Phormidium tenue species produced a bio-crust that prevent soil erosion.